2017
DOI: 10.1039/c7md00486a
|View full text |Cite
|
Sign up to set email alerts
|

Novel T-C@AgNPs mediated biocidal mechanism against biofilm associated methicillin-resistant Staphylococcus aureus (Bap-MRSA) 090, cytotoxicity and its molecular docking studies

Abstract: is a commonly found pathogen that can cause food-spoilage and life threatening infections. However, the potential molecular effects of natural active thymol molecules and chitosan silver nanoparticles (C@AgNPs) in bacteria remain unclear. This gap in the literature has prompted us to study the effects of thymol loaded chitosan silver nanoparticles (T-C@AgNPs) against biofilm associated proteins in methicillin-resistant (Bap-MRSA) 090 and also their toxicity, anti-cancer activity, and validation of their molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…This confirmed that, the designed compound was specific to the PLA2 which intern suggests the route for synthesis of target drug. [33][34][35][36] The designed compound 3 (P1C) and P1C-Tit*CAgNPs also showed moderate anticancer properties without affecting the normal physiology, and their inhibitory effects on the inflammatory progression were validated in this study.…”
Section: Discussionmentioning
confidence: 83%
“…This confirmed that, the designed compound was specific to the PLA2 which intern suggests the route for synthesis of target drug. [33][34][35][36] The designed compound 3 (P1C) and P1C-Tit*CAgNPs also showed moderate anticancer properties without affecting the normal physiology, and their inhibitory effects on the inflammatory progression were validated in this study.…”
Section: Discussionmentioning
confidence: 83%
“…In a recent study, Manukumar et al described the efficacy of thymol-loaded chitosan silver nanoparticles (T-C@AgNPs) against biofilm producing MRSA using disc diffusion method. Using different concentrations of T-C@AgNPs from 10, 25, 50, 100, 200, and 250 μg/mL and comparing the concentration that produced 10.08±0.06 mm of zone of inhibition (ZOI) with the standard antibiotic ciprofloxacin (10 μg) that had 10.95±0.08 mm ZOI, a dose-dependent biocidal and anti-biofilm activity was found 86. Another recent study also described the antibacterial activity of benzodioxane midst piperazine decorated chitosan silver nanoparticles (BP*C@AgNPs).…”
Section: Introductionmentioning
confidence: 99%
“…Their solubility and biological reactivity have restricted their applications to simple disinfectants in the past, but now nanoparticulate forms of these metals are available. Of these metals, silver nanoparticles are arguably the strongest biocide with minimum inhibitory concentrations (MICs) of 3.25 mg/L to Streptcoccus mutans 19 and silver nanoparticles are also toxic to S. aureus when silver is presented as a filler in chitosan20,21 or a coating on medical grade titanium alloy 22…”
Section: Introductionmentioning
confidence: 99%